2010
DOI: 10.1371/journal.pone.0013833
|View full text |Cite
|
Sign up to set email alerts
|

A Voltage-Sensitive Dye-Based Assay for the Identification of Differentiated Neurons Derived from Embryonic Neural Stem Cell Cultures

Abstract: BackgroundPluripotent and multipotent stem cells hold great therapeutical promise for the replacement of degenerated tissue in neurological diseases. To fulfill that promise we have to understand the mechanisms underlying the differentiation of multipotent cells into specific types of neurons. Embryonic stem cell (ESC) and embryonic neural stem cell (NSC) cultures provide a valuable tool to study the processes of neural differentiation, which can be assessed using immunohistochemistry, gene expression, Ca2+-im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
0
13
0
1
Order By: Relevance
“…Most studies on neuronal differentiation processes still rely on classical qualitative or quantitative endpoint analysis of neuronal marker genes/proteins, which depend on time-and costconsuming cell labeling and destruction of the analyzed sample (Mertens et al 2015;Pasca et al 2015), while electrophysiological analysis of neuronal activity is only suitable for matured cultures after several weeks/months (Heikkila et al 2009;Mertens et al 2015;Ullah et al 2016). Although, there is ongoing research to overcome these limitations, existent studies as well require artificial handling such as cell isolation or genetic manipulation and are thus not able to assure and predict the progress of neuronal maturation of a complex iPS-derived neural network (Ilieva et al 2013;Leao et al 2010;Mir and Shinohara 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies on neuronal differentiation processes still rely on classical qualitative or quantitative endpoint analysis of neuronal marker genes/proteins, which depend on time-and costconsuming cell labeling and destruction of the analyzed sample (Mertens et al 2015;Pasca et al 2015), while electrophysiological analysis of neuronal activity is only suitable for matured cultures after several weeks/months (Heikkila et al 2009;Mertens et al 2015;Ullah et al 2016). Although, there is ongoing research to overcome these limitations, existent studies as well require artificial handling such as cell isolation or genetic manipulation and are thus not able to assure and predict the progress of neuronal maturation of a complex iPS-derived neural network (Ilieva et al 2013;Leao et al 2010;Mir and Shinohara 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Besides time-consuming conventional molecular biological methods mainly restricted to end-point analysis, some techniques have emerged that allow the fast and real-time study of differentiating cell lines. However, these technologies are mostly dependent on labels or single cell applications that do not comprise the analysis of a complex developing neuronal network (Leao et al 2010;Mir and Shinohara 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For imaging, the transplants were removed from live animals and cut on a vibratome with 200‐μm slices, which were transferred to the stage of an upright microscope and continuously perfused with aCSF with no HEPES equilibrated with 95% O 2 + 5% CO 2 . Excitation was provided by a light‐emitting diode array [11]. For VSFP2.42 imaging, excitation was centered at 520 nm, and a 605 nm low‐pass filter was used for emission, thus avoiding cross‐talk from EGFP fluorescence emission.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate if NSCs grown on 4RepCT foam shaped matrices in 3D can differentiate into neurons we exposed the cells to treatment with bone morphogenetic protein (BMP) 4 or co-treatment with BMP4 and the signaling factor Wnt3a for 14 days. We have previously shown that BMP4 and BMP4+Wnt3a stimulation induces differentiation of mature, functional glutamate-receptor (GluR) -agonist responsive neuronal cells when NSCs are seeded at relatively high densities [16,25]. NSCs grown in 3D on 4RepCT foam matrices with pore sizes of around 5-30 µm and exposed to 10 ng/ml BMP4 or BMP4 and Wnt3a every 24 hours for 14 days differentiated into neuronal cells positive for the dendritic marker of mature, post-mitotic neurons, microtubule associated protein 2 (MAP2; in average 30 cells/5 micrographs/well (BMP4) and 41 cells/5 micrographs/well (BMP4+Wnt3a) in control conditions, and 71 cells/5 micrographs/well (BMP4) and 94 cells/5 micrographs/well (BMP4+Wnt3a) when grown on 4RepCT foam) (Figure 1,2).…”
Section: Repct Foam Structures Provide Efficient Substrates For Neurmentioning
confidence: 99%